2023
DOI: 10.5888/pcd20.220403
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Insufficient Sleep, Depressive Symptoms, and Suicidality Among Florida High School Students

Abstract: Introduction Emerging research suggests insufficient sleep can heighten the risk of poor mental health among adolescents. We examined the relationship between sleep, depressive symptoms, and suicidal thoughts and behaviors among Florida high school students. Methods Data were from the 2021 Florida High School Youth Risk Behavior Survey, a statewide representative sample of students in grades 9 to 12. We estimated prevalence of 1 indicator of depressive symptoms — feelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…High school students may have fewer hours of sleep and physical activity on weekdays due to homework loads and earlier school days. Gunderson J's [59] study found that more than three-quarters (78.4%) of students do not get eight hours or more of sleep on school nights. Our study found that high school students were less likely to be physically active for the recommended amount of time compared to middle school students.…”
Section: Discussionmentioning
confidence: 99%
“…High school students may have fewer hours of sleep and physical activity on weekdays due to homework loads and earlier school days. Gunderson J's [59] study found that more than three-quarters (78.4%) of students do not get eight hours or more of sleep on school nights. Our study found that high school students were less likely to be physically active for the recommended amount of time compared to middle school students.…”
Section: Discussionmentioning
confidence: 99%